Effect of a distal attachment cuff on adenoma detection rate in screening colonoscopy: Randomized controlled trial in the Spanish population - Burgos García, Aurora; Herreros de Tejada, Alberto; Ferre Aracil, Carlos; Nogales, Oscar; Parejo, Sofía; Tavecchia, Mariana; Agudo, Belen; Canaval Zuleta, Héctor Julián; Cañete Ruiz, Angel; De Frutos Rosa, Diego; Arribas Anta, Julia; Peñas, Beatriz; Borobia, Rodrigo; Mendoza, Juan L; Bernardo, Cristina; De María, Pedro; Lopez Palacios, Natalia; Jiménez Gómez, Mirella; Cacho Acosta, Guillermo; Cuadros Martínez, Marta; Mayor Delgado, Patricia; Ruiz Ramírez, María Ángeles; Royuela Vicente, Ana; Rodriguez de Santiago, Enrique; Froilán, Consuelo (Endoscopy International Open, 2025)
Endocuff Vision (EV) is a disposable device designed to improve polyp detection. The primary aim of this study was to evaluate the effect of EV on adenoma detection rate (ADR) and mean number of adenomas per patient (MAP).This multicenter randomized controlled trial compared EV-assisted colonoscopy (EAC) and standard colonoscopy (SC). Patients were referred due to a positive fecal immunochemical test (FIT) in a bowel cancer screening program (BCSP), direct screening colonoscopy without prior FIT, surveillance colonoscopy, or family history of colorectal cancer.In total, 1437 patients (55.9% male; median age, 59 years) were randomized at eight Spanish university hospitals. No significant differences were found in either the ADR (EAC vs. SC, 55.8% vs. 54.3%; P = 0.576) or the MAP (1.60 vs. 1.35; P = 0.03). Compared with SC, EAC was not associated with a significant improvement in detection rates for advanced adenomas, sessile serrated lesions, or advanced sessile serrated lesions. There was no difference in cecal intubation rate but the successful ileal intubation rate, among patients in whom it was attempted, was lower with EAC (64.3% vs. 86.5% with SC; P = 0.001).EV did not improve either ADR or MAP. EV may increase difficulty of ileal intubation whenever it is attempted.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; Colorectal cancer; CRC screening